2007
DOI: 10.1007/s11065-007-9041-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Consequences of Opiate Use

Abstract: Approximately 3.7 million individuals have used heroin and other opiate substances in their lifetime. Despite increasing knowledge of the effects of heroin, it remains the most abused opiate and use among adults has recently increased. The empirical literature examining the neurocognitive effects of acute and chronic opioid use remains limited; however, findings to date suggest that the use of opiates has both acute and long-term effects on cognitive performance. Neuropsychological data indicate deficits in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 95 publications
6
79
1
1
Order By: Relevance
“…Clinical research has shown that opiate addicts display deficits in memory tasks, attention, verbal fluency, and general cognitive performance, relative to controls (Cipolli and Galliani, 1987;Guerra et al, 1987;Gruber et al, 2007). The possibility that chronic opiate treatment in nonaddicted patients may also cause cognitive impairment in the long term is controversial, but is of considerable clinical interest (Kendall et al, 2010;Kurita et al, 2011;Højsted et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research has shown that opiate addicts display deficits in memory tasks, attention, verbal fluency, and general cognitive performance, relative to controls (Cipolli and Galliani, 1987;Guerra et al, 1987;Gruber et al, 2007). The possibility that chronic opiate treatment in nonaddicted patients may also cause cognitive impairment in the long term is controversial, but is of considerable clinical interest (Kendall et al, 2010;Kurita et al, 2011;Højsted et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Opiates mediate their reinforcing actions via a family of G-protein-coupled receptors, which are commonly classified into major subtypes designated m, d, k, and orphaninFQ/ nociceptin (Minami and Satoh 1995;von Zastrow 2004;Le Merrer et al 2009). It is their binding to these receptors-the m (and to a lesser extent d) opioid subtype, in particularthat is thought to be responsible for their positive reinforcing properties (Gruber et al 2007;Le Merrer et al 2009). Although these receptors are found in a large number of brain structures (Mansour et al 1988;Le Merrer et al 2009), the direct reinforcing effects of opioids appear to be limited to a select number of brain areas.…”
Section: Opiate Reward and Reinforcement In The Brainmentioning
confidence: 99%
“…However, many of these compounds-for example, heroin and other opiates-are among the most addictive drugs in human history (Kalant 1997;Gruber et al 2007). For these and other reasons, the elucidation of their motivational mechanisms of action has remained a priority for many researchers.…”
mentioning
confidence: 99%
“…There is a relative lack of empirical studies examining deficits in executive function specific to opiate addicts (Feil et al, 2010, Gruber et al, 2007. However, a growing body of evidence has demonstrated impaired performance among opiate dependent subjects on executive measures including; the Stroop Task, Ruff Figural Fluency Test, Go/No go task, measures of impulsivity, gambling tasks, delay discounting tasks, attention, and working memory (Brand et al, 2008;Fishbein et al, 2007;Forman et al 2004;Kirby & Petry, 2004;Mintzer & Stitzer, 2002;Ornstein et al, 2000;Rapeli et al, 2006;Pirastu et al, 2006).…”
Section: Impairment Of Executive Function In Opiate Dependencementioning
confidence: 99%